Generasi Milenial di Media Sosial: Antisipasi Terhadap Arus Radikalisme - Kholifah, Latif Nur; Sari, Maula (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
Abstract The current millennial generation must prefer to take information because acts of radicalism are increasingly accessible on social media. see the number of millennials who have fallen into this act of radicalism. This paper aims to find out what things must be done to anticipate radicalism from social media. The method used in this research is the research method used in this research literature review or library research using descriptive analysis. This method presents a variety of data and facts in a number of literatures, both primary and secondary. This study aims to explore data through reference books, journals, and data on social media. The results of the study show that the way to anticipate the millennial generation against radicalism is; Realize that Islam is harmonious, Recognize the meaning of jihad, There is no guarantee that a suicidal person will go to heaven, Recognize hadith and verses of the Koran wisely on social media.